The lure of perfection : fashion and ballet, 1780-1830 - Chazin-Bennahum, Judith (Routledge, 2005)
THE LURE OF PERFECTION: FASHION AND BALLET, 1780-1830 offers a unique look at how ballet influenced contemporary fashion and women's body image, and how street fashions in turn were reflected by the costumes worn by ballet dancers. Through years of research, the author has traced the interplay between fashion, social trends, and the development of dance. During the 18th century, women literally took up twice as much space as men; their billowing dresses ballooned out from their figures, sometimes a full 55 inches, to display costly jewelry and fine brocade work; similar costumes appeared on st.